Study Habit and Social Media Exposure as Predictors of Grade 10 Students Academic Performance - Castillas, Glenn M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this study was to determine the respondents' study habits and social media exposure during the school year. 2019-2020.The study's participants were 50 grade 10 students of Alabel 4 District. The researcher administered the survey to all of the student respondents. Majority of respondents were 17 years old, and the majority of their parents had a bachelor's degree and were all employed. The researcher administered the survey to all of the student respondents. The majority of respondents were 17 years old, and the majority of their parents had a bachelor's degree and were all employed. It also has a high correlation with respondents' social media exposure. The responses revealed that respondents' use of social media has a direct or indirect positive effect on their academic performance. The study suggests that parents should constantly guide and supervise their children's use of social media, particularly female and younger students who are more interested in social networking. Despite the fact that this study discovered that respondents' socio-demographic characteristics have no bearing on their academic performance. It also suggests that a long-term program be implemented to assist students in constantly improving their study habits. According to the study's findings, teachers must continue to effectively stimulate and sustain students' interests and enthusiasm for learning in order for them to consistently achieve exceptional academic performance. Teachers should receive regular service trainings and workshops to stay current on their knowledge and pedagogical skills, improve the quality of the teacher workforce, and improve students' academic achievement.